Do Nutrition Education Approaches With Preschoolers and Their Caregivers Influence Retention of Biofortified Orange-Fleshed Sweetpotato on Farms?: Evidence From Homa Bay County, Kenya - Ojwang, S.O.; Otieno, David Jakinda; Okello, J.J.; Muoki, Penina Ngusye; Nyikal, R.A. (SAGE Publications, 2021)
Background: Biofortified staples have been promoted widely in sub-Saharan Africa to combat micronutrient deficiencies. Contemporary projects are increasingly using elementary schools to target households with these foods. Objective: This study assessed the effects of integrated nutrition education approaches, targeting preschoolers and their caregivers, on retention of orange-fleshed sweetpotato (OFSP) on farms in the second season after lapse of free vine dissemination initiatives. Methods: Rural farming households, with preschoolers and no prior engagement with OFSP, were targeted. A multistage sample of 431 preschooler-caregiver pairs was recruited for a cluster-randomized controlled trial. After issuing routine OFSP promotion activities, 15 village-level clusters of the pairs were randomized into 1 control group (3 villages) and 3 treatment arms (4 villages each) for the interventions. Baseline and follow-up household-level survey data were collected from the caregivers. The interventions included: (1) OFSP-branded exercise books, posters, and a poem to preschoolers only; (2) OFSP-oriented mobile phone-mediated text messages to caregivers only; and (3) both 1 and 2 provided to individual households concurrently. Interventions 1 and 2 were single-channeled, while 3 was multichanneled. We estimated the intention-to-treat (ITT) and treatment-on-the-treated (TOT) effects using a binary logit model and a special regressor method, respectively. Results: Only the multichanneled nutrition education approach had significant effects (ITT = 0.167, P = .001; TOT = .243, P = .007) on the caregivers' likelihood to retain OFSP on their farms. Conclusions: The finding implies that multichanneled agriculture-nutrition education interventions through Early Childhood Development institutions can be effective in ensuring sustainable adoption of OFSP.